Mechanism of steel slag powder stabilization and improvement of expansive clay - Yinlei SUN; Chuan YU; Lei LIAO; Zhifei LI (Shuiwen dizhi gongcheng dizhi)
Expansive clay is prone to geological disasters such as roadbed deformation, slope instability, and landslides under long-term hot and humid conditions. To address these engineering challenges and promote the high-value, resource-efficient use of steel slag, it is crucial to investigate the macroscopic and microscopic characteristics of steel slag powder (SSP)-improved expansive clay. This paper provides a comprehensive review of the current research on SSP-improved expansive clay, systematically summarizing the physicochemical properties and gelling activity of SSP. Additionally, the excitation principle of alkali exciters on the activity of SSP was described, and the micro-mechanism and mechanical properties of SSP improved expansive clay were revealed. The main conclusions are as follows: (1) SSP contains abundant active mineral components that can undergo ion exchange and hydration reaction with clay particles, thus changing the microstructure and physicochemical properties of clay. (2) The chemical composition and structural properties of SSP will be affected by the production process and the use of the environment, which in turn affects its chemical activity. By reducing the particle size of SSP, adding alkaline exciters or compound modification can improve its cementation activity and hydration rate. (3) SSP as a soil conditioner can significantly improve the performance of expansive clay, including expansion and contraction and mechanical properties. (4) The studies on the interaction mechanism between SSP and clay and the application effect of composite exciters remain insufficient and requires further investigation. (5) Future research should consider the chemical and physical properties under the coupling of different factors, including the chemical-mineral composition and the microstructure evolution law of the soil, as well as the mechanical properties of the soil under the water-chemical-force interactions. By further exploring the micro-mechanism and engineering properties of SSP-amended soils, the value of their engineering applications can be improved, providing valuable insights for the recycling of solid waste resources and environmental protection.